High-output diesel engine heat transfer: Part 1 - comparison between piston heat flux and global energy balance. (August 2022) - Gingrich, Eric; Tess, Michael; Korivi, Vamshi; Ghandhi, Jaal
High-output diesel engine heat transfer measurements are presented in this paper, which is the first of a two-part series of papers. Local piston heat transfer, based on fast-response piston surface temperature data, is compared to global engine heat transfer based on thermodynamic data. A single-cylinder research engine was operated at multiple conditions, including very high-output cases – 30 bar IMEPg and 250 bar in-cylinder pressure. A wireless telemetry system was used to acquire fast-response piston surface temperature data, from which heat flux was calculated. An interpolation and averaging procedure was developed and a method to recover the steady-state portion of the heat flux based on the in-cylinder thermodynamic state was applied. The local measurements were spatially integrated to find total heat transfer, which was found to agree well with the global thermodynamic measurements. A delayed onset of the rise of spatially averaged heat flux was observed for later start of injection timings. The dataset is internally consistent, for example, the local measurements match the global values, which makes it well suited for heat transfer correlation development; this development is pursued in the second part of this paper.